XRCC1 Gene Polymorphisms and the Risk of Differentiated Thyroid Carcinoma (DTC): A Meta-Analysis of Case-Control Studies - Bao, Yi (Public Library of Science, 2013)
BACKGROUND: Previous studies investigating the association between X-ray repair cross-complementing group 1 (XRCC1) polymorphisms and thyroid cancer risk have yielded inconsistent results. This meta-analysis was performed to derive a more precise estimation of the relationship between three XRCC1 polymorphisms and thyroid cancer risk. METHODS/PRINCIPAL FINDINGS: PubMed and EMBASE database were systematically searched to identify relevant studies. 10 publications were selected for this meta-analysis, including 11 studies for Arg399Gln polymorphism (1726 cases and 3774 controls), 7 studies for Arg194Trp polymorphism (1037 cases and 2487 controls) and 8 studies for Arg280His polymorphism (1432 cases and 3356 controls). The results in total population did not show any significant association between these three polymorphisms and the risk of DTC for all genetic models. However, when stratified by ethnicity, the results showed that Arg280His polymorphism was associated with an increased risk of DTC among Caucasians (Arg/His vs. Arg/Arg: OR = 1.45, 95% CI = 1.09–1.93; dominant model: OR = 1.43, 95% CI = 1.08–1.89; additive model: OR = 1.38, 95% CI = 1.05–1.80), whereas individuals carrying Arg/His genotype have a significantly reduced risk of DTC among Asians (Arg/His vs. Arg/Arg: OR = 0.71, 95% CI = 0.51–0.98). We also detected that 399Gln variant allele carriers might presented an overall decreased risk of DTC in mixed population. Furthermore, subgroup analyses by histological subtype revealed that Arg194Trp polymorphism was significantly associated with reduced risk for papillary thyroid carcinoma (PTC) (dominant model: OR = 0.71, 95% CI = 0.50–0.99). CONCLUSIONS: This meta-analysis suggests that Arg280His polymorphism might contribute to the susceptibility of DTC among Caucasians, whereas it might provide protective effects in Asians against the risk of DTC. Additionally, our results support the protective role of Arg194Trp polymorphism in developing PTC, and show evidence of an association between Arg399Gln polymorphism and decreased risk of DTC in mixed population.